1999
DOI: 10.1002/(sici)1097-4644(19990915)74:4<628::aid-jcb12>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of HPV11 L1 capsid protein is mediated by karyopherin α2β1 heterodimers

Abstract: L1 major capsid proteins of human papillomaviruses (HPVs) enter the nuclei of host cells at two times during the viral life cycle: 1) after infection and 2) later during the productive phase, when they assemble the replicated HPV genomic DNA into infectious virions. L1 proteins are stable in two oligomeric configurations: as homopentameric capsomers, and as capsids composed of 72 capsomers. We found that intact L1 capsids of HPV type 11 cannot enter the nucleus, suggesting that capsid disassembly may be requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Our first goals were to examine the nuclear entry of the PV genome and its possible continued association with L1 and͞or L2 as well as where in the cell the initial uncoating took place. We expected that at least partial disassembly of the viral particle would occur before nuclear import, because it has been reported that intact human PV capsids are unable to enter the nucleus (27,28). Consistent with this possibility, initial analyses of HeLa cells infected with BPV-1 virus or pseudovirus showed no evidence of nuclear L1 with any of several tested L1 antibodies or fixation conditions (data not shown).…”
Section: Resultsmentioning
confidence: 55%
“…Our first goals were to examine the nuclear entry of the PV genome and its possible continued association with L1 and͞or L2 as well as where in the cell the initial uncoating took place. We expected that at least partial disassembly of the viral particle would occur before nuclear import, because it has been reported that intact human PV capsids are unable to enter the nucleus (27,28). Consistent with this possibility, initial analyses of HeLa cells infected with BPV-1 virus or pseudovirus showed no evidence of nuclear L1 with any of several tested L1 antibodies or fixation conditions (data not shown).…”
Section: Resultsmentioning
confidence: 55%
“…In the nucleus, binding of RanGTP to Kap ␤1 dissociates the import complex with release of HPV16 L1⅐Kap ␣2. We had previously established that the L1 proteins of low risk HPV11 and high risk HPV45 can interact with Kap ␣2 and enter the nucleus via the classic Kap ␣2␤1-mediated pathway (38,39). Six Kap ␣ isoforms have been identified in higher eukaryotes, and they all bind to the same Kap ␤1.…”
Section: Discussionmentioning
confidence: 99%
“…Although HeLa cells are HPV18-positive, this does not affect the import properties of their nuclear pore complexes, as demonstrated by the fact that the majority of nuclear import pathways have been identified and characterized with HeLa cells (20, 22, 30 -38). We have previously used these in vitro nuclear import assays in HeLa cells to investigate import of HPV11 L1 and HPV45 L1 major capsid proteins (38,39). In the present study, subconfluent HeLa cells, grown on poly-L-lysine-coated glass coverslips for 24 h, were permeabilized with 70 g/ml digitonin for 5 min on ice and washed with buffer A. Digitonin permeabilizes the plasma membrane but leaves the nuclear envelope intact.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For reconstitution experiments, purified recombinant importin-␣2 (0.125 mg/ml) and/or importin-␤ (0.125 mg/ml) were added to the cytosol depleted of the importins. For the docking assay, recombinant importin-␤ was used as a source of import factor instead of HeLa cell cytosol, as previously described (30,33,34).…”
Section: Methodsmentioning
confidence: 99%